Understanding the coherent dynamic structure factor of liquid water measured by neutron spectroscopy with polarization analysis: a Molecular Dynamics simulations study - Alvarez Fernando; Arbe Arantxa; Colmenero Juan (EPJ Web of Conferences, 2022)
This work is focused on atomistic molecular dynamics (MD) simulations of water carried out at 300 K. The main goal is to better understand the experimental results of the coherent dynamic structure factor S(Q,ν) of D2O that were obtained by means of neutron scattering with polarization analysis and previously reported by us [A. Arbe et al. Phys. Rev. Res. 2, 022015 (2020)]. From the simulations, we have calculated the coherent dynamic structure factor in the time domain S(Q,t) as well as its selfand distinctcontributions. We have also calculated S(Q,t) corresponding to a H2O sample. The main results obtained are: (i) The Q-independent relaxation process identified in S(Q,ν) in the mesoscopic range (Q0-mode) is the responsible of the restructuring of the hydrogen bond (HB) network at times shorter than that corresponding to the molecular diffusion; (ii) the vibrational contribution identified at high frequency in S(Q,ν) corresponds to a hydrodynamic-like mode propagating in an elastic medium (fixed HB bonding pattern); (iii) in the crossover range from mesoscopic to intermolecular scales, diffusion also progressively contributes to the decay of density fluctuations; (iv) MD-simulations suggest that it would be basically impossible to measure S(Q,ν,) of H2O in the mesoscopic range with the current neutron scattering capabilities.